Pharmacokinetics of pediatric lopinavir/ritonavir tablets in children when administered twice daily according to FDA weight bands - Diane E.T. Bastiaans (2018)
© 2013 by Lippincott Williams & Wilkins. Background: Lopinavir/ritonavir (LPV/r) pediatric tablets (100/25 mg) are approved by the United States Food and Drug Administration (FDA) and European Medicines Agency (EMA) as part of combination antiretroviral therapy. Dosing is based on body weight bands or body surface area under FDA approval and only body surface area by the EMA. This can lead to a different recommended dose. In addition, weight band.based dosing has not been formally studied in the target population. We evaluated the pharmacokinetics (PK) of LPV/r in children, administered twice daily according to the FDA weight bands, using pediatric tablets. Methods: Fifty-three HIV-infected children were included in the PK substudy of the Paediatric European Network for the Treatment of AIDS 18 trial (KONCERT). In this study, children were randomized to receive LPV/r twice or once daily, according to FDA weight bands. A PK assessment was performed in 17, 16 and 20 children in the 15.25 kg, ≥25.35 kg and >35 kg weight band, respectively, while children took the tablets twice daily. Rich sampling was performed, and PK parameters were calculated by noncompartmental analysis. Given the high percentage of Asian children, it was also tested whether there was a difference in PK parameters between Asian and non-Asian children. Results: For the total group, LPV geometric mean AUC0.12, Cmaxand C12were 106.9 h × mg/L, 12.0 mg/L and 4.9 mg/L, respectively. There were no significant differences in LPV PK parameters between the weight bands. In addition, weight was not found to be associated with variability in Cmax, C12or AUC0.12for the LPV PK parameters. Conclusions: FDA weight band.based dosing recommendations provide adequate exposure to LPV when using LPV/r pediatric tablets.